2010
DOI: 10.1111/j.1365-246x.2009.04399.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of the stress state in a supercontinent during mantle reorganization

Abstract: S U M M A R YPrevious numerical simulation models of isoviscous mantle convection in both 2-D and 3-D geometries have revealed that the presence of a supercontinental lid produces large-scale horizontal mantle flow, thereby reorganizing the thermal structure of the mantle interior. Large-scale upwelling plumes arising from the core-mantle boundary (CMB) beneath the supercontinent are observed in some models. These upwelling plumes have been hypothesized to produce tensional stresses in the supercontinent and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 91 publications
1
11
0
1
Order By: Relevance
“…In this work, we choose the 100 MPa as the default yield strength of the continental lithosphere. The value is consistent with previous dynamic works (e.g., Yoshida, ; Mallard et al, ).…”
Section: Numerical Model Setupsupporting
confidence: 93%
“…In this work, we choose the 100 MPa as the default yield strength of the continental lithosphere. The value is consistent with previous dynamic works (e.g., Yoshida, ; Mallard et al, ).…”
Section: Numerical Model Setupsupporting
confidence: 93%
“…It is widely accepted in geodynamics community that the viscosity contrast between the upper and lower mantles is around 30 mainly on the basis of a series of geoid inversion studies with isoviscous geodynamic model [ Hager , 1984; Hager and Clayton , 1989; Hager and Richards , 1989]. In the present model with the viscosity contrast (Δ η 660 ) of 30 under both dry and wet conditions in the MTZ, however, the plate stagnation in the MTZ is more transient than in the models with Δ η 660 = 100, as demonstrated by high‐resolution numerical simulations of 3D spherical mantle convection with an appropriate temperature‐dependent rheology [e.g., Kennett and Bunge , 2008; Yoshida , 2010a]. Furthermore, the recent geoid inversion studies with horizontally variable viscosity, which focused on the positive geoid anomaly in the subduction zones, suggested that Δ η 660 is likely to be substantially greater than 30, say, on the order of 100 [ Tosi et al , 2009; Yoshida and Nakakuki , 2009].…”
Section: Discussionmentioning
confidence: 99%
“…They now include a basic model of continental lithosphere (Yoshida, 2010;Rolf and Tackley, 2011), modeled as thick and buoyant rafts, being 100 times more viscous than oceanic lithosphere. In this study, we computed numerical solutions in spherical geometry with a spherical cap-shaped continent covering 10%, 30%, 50%, or 70% of the surface (both of the latter percentages are probably higher than ever existed on Earth) and without any continent.…”
Section: Convection Models With Continents and Seafloor Spreadingmentioning
confidence: 99%